الفروق الفقهية عند المالكية من خلال كتاب التنبيه على مبادئ التوجيه - نماذج مختارة - غمام جريد, ادريس (University of eloued جامعة الوادي, 2021)
البحث الذي بين أيدينا هو بعنوان الفروق الفقهية عند المالكية من خلال كتاب التنبيه على مبادئ التوجيه -نماذج مختارة-؛ قمتُ بجمع المسائل المتشابهة في الصورة والمختلفة في الحكم، وقد اشتمل البحث على مبحثين وخاتمة فخصصتُ المبحث الأول للقسم النظري لعلم الفروق الفقهية تناولتُ فيه: تعريف الفروق الفقهية، وترجمة موجزة لابن بشير وأهمية الفروق الفقهية ونشأتها، وعلاقتها بغيرها، وأهم المؤلفات فيها عند المذاهب الأربعة وأهم الرسائل العلمية لعلم الفروق الفقهية. وأما المبحث الثاني فخصصته للدراسة التطبيقية للفروق الفقهية الواردة في الكتاب، وفيه أربعة مطالب قسمتها على الأبواب التالية: (الطهارة والصلاة والصيام والزكاة).This research is entitled: Fiqh Differences of the Malikis, through the book: "Alert on the Principles of Guidance" -collecting and studying-. I collected similar issues in the picture and different in judgment, and the research included two sections and a conclusion. The first section was devoted to the theoretical section of the science of fiqh differences, in which I dealt with: the definition of fiqh differences, a brief translation of Ibn Bashir, the importance of fiqh differences and their emergence, and their relationship to others, and the most important literature in them when The four schools of thought and the most important scientific treatises for the science of fiqh differences. As for the second topic, it was devoted to the applied study of the fiqh differences mentioned in the book, and it contains four demands; I divided it into the following chapters: (Purity, prayer, fasting and zakat).
مذكرة ماستر
Keywords: الفروق الفقهية، المالكية، التنبيه على مبادئ التوجيه.; Differences jurisprudence, Malikis, alerting the principles of guidance.